Intelligence and Security Informatics Pacific Asia Workshop, PAISI 2009, Bangkok, Thailand, April 27, 2009. Proceedings - Chen, Hsinchun; Yang, Christopher C.; Chau, Michael; Li, Shu-Hsing (Security and Cryptology, 2009)
This book constitutes the refereed proceedings of the Pacific Asia Workshop on Intelligence and Security Informatics, PAISI 2009, held in Bangkok, Thailand, in April 2009. The 10 revised full papers, 7 revised short papers together with 1 keynote lecture were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on terrorism informatics and crime analysis enterprise risk management emergency response and surveillance information access and security, as well as data and text mining.